The earliest-known mammaliaform fossil from Greenland sheds light on origin of mammals - Sulej, Tomasz (Proc Natl Acad Sci U S A, 2020)
Synapsids are unique in having developed multirooted teeth and complex occlusions. These innovations evolved in at least two lineages of mammaliamorphs (Tritylodontidae and Mammaliaformes). Triassic fossils demonstrate that close to the origins of mammals, mammaliaform precursors were “experimenting” with tooth structure and function, resulting in novel patterns of occlusion. One of the most surprising examples of such adaptations is present in the haramiyidan clade, which differed from contemporary mammaliaforms in having two rows of cusps on molariform crowns adapted to omnivorous/herbivorous feeding. However, the origin of the multicusped tooth pattern present in haramiyidans has remained enigmatic. Here we describe the earliest-known mandibular fossil of a mammaliaform with double molariform roots and a crown with two rows of cusps from the Late Triassic of Greenland. The crown morphology is intermediate between that of morganucodontans and haramiyidans and suggests the derivation of the multicusped molariforms of haramiyidans from the triconodont molar pattern seen in morganucodontids. Although it is remarkably well documented in the fossil record, the significance of tooth root division in mammaliaforms remains enigmatic. The results of our biomechanical analyses (finite element analysis [FEA]) indicate that teeth with two roots can better withstand stronger mechanical stresses like those resulting from tooth occlusion, than teeth with a single root.